1997
DOI: 10.1074/jbc.272.13.8764
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression of a Bovine α(1,3)-Fucosyltransferase Gene Homologous to a Putative Ancestor Gene of the Human FUT3-FUT5-FUT6 Cluster

Abstract: Cell surface fucosylated oligosaccharides have received a substantial amount of attention because they play a role in inflammation-mediated cell adhesion and are frequently mod-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 53 publications
4
40
0
Order By: Relevance
“…These acceptors were: (i) the disaccharide precursor of type 1, which can incorporate fucose in ␣1,2-linkage on the terminal Gal and in ␣1,4-linkage on the internal GlcNAc and (ii) the unambiguous trisaccharide H type 1, which can only incorporate fucose in the ␣1,4 position on the internal GlcNAc. This last trisaccharide was the better acceptor and it was more than twice as efficient as the disaccharide, confirming previous results (35,36). The 314 mutated construct gave results similar to the wild type FUT3 construct and no enzyme activity could be detected with either of the 1067 mutated or the double mutated 202-314 constructs, in good accordance with the fluorescence results (Table I).…”
Section: Molecular Cloning Of Wild Mutated and Chimeric Fut3supporting
confidence: 80%
See 1 more Smart Citation
“…These acceptors were: (i) the disaccharide precursor of type 1, which can incorporate fucose in ␣1,2-linkage on the terminal Gal and in ␣1,4-linkage on the internal GlcNAc and (ii) the unambiguous trisaccharide H type 1, which can only incorporate fucose in the ␣1,4 position on the internal GlcNAc. This last trisaccharide was the better acceptor and it was more than twice as efficient as the disaccharide, confirming previous results (35,36). The 314 mutated construct gave results similar to the wild type FUT3 construct and no enzyme activity could be detected with either of the 1067 mutated or the double mutated 202-314 constructs, in good accordance with the fluorescence results (Table I).…”
Section: Molecular Cloning Of Wild Mutated and Chimeric Fut3supporting
confidence: 80%
“…We have in parallel cloned and sequenced the corresponding FUT3, FUT5, and FUT6 genes of the chimpanzee 3 and the bovine futb gene (35), and aligned these sequences with the human FUT3, FUT5, and FUT6 sequences. The tryptophan residue at position 68, which is affected by the T202C mutation of human Fuc-TIII, is conserved in the corresponding positions of the three human, three chimpanzee, and bovine Fuc-Ts.…”
Section: Molecular Cloning Of Wild Mutated and Chimeric Fut3mentioning
confidence: 99%
“…Interestingly, the three members of the ␣3/4-fucosyltransferase family co-localized to chromosome 19 are highly similar in sequence. These appear to have been duplicated very recently, because only one gene for this cluster was found in the cow (64). Two more divergent members of this family are localized differently.…”
Section: Isolation and Characterization Of Human C2/4gnt-analysis Of mentioning
confidence: 99%
“…The position of this futb gene in the phylogenetic tree of fucosyltransferases, showed that the separation of the bovine species from the common evolutionary pathway, during the great mammalian radiation some 80 million years ago, occurred before the duplication events, which originated the present cluster of human FUT3, FUT5, and FUT6 genes and suggested that this bovine enzyme is the orthologous homologue of the ancestor of the FUT3, FUT5, and FUT6 human genes (6).…”
mentioning
confidence: 99%